How can the use of Rubrics contribute to make assessment a transparent process a ninth grade course at Institución Educativa Concejo de Medellín? (2018)
ABSTRACT: This action research study reports how the use of rubrics can contribute with a transparent assessment process in a 9th grade course at a public institution in Medellin, Colombia. The actions developed during the process were: choosing a general topic to work with, dividing the topic in three stages, designing three different types of rubrics, and applying them one by one at the end of each stage. Data collection techniques combine one survey to the students at the beginning, the teacher’s journal, and one interview to the students at the end of the whole process. Findings revealed that using rubrics as a teaching tool to assess students, allowed them to obtained better results in their language acquisition processes, due to the students’ knowledge of clear criteria that allow them to achieve the proposed objectives.